2019
DOI: 10.1108/lht-10-2017-0218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Google question-answering quality

Abstract: Purpose The purpose of this paper is to evaluate Google question-answering (QA) quality. Design/methodology/approach Given the large variety and complexity of Google answer boxes in search result pages, existing evaluation criteria for both search engines and QA systems seemed unsuitable. This study developed an evaluation criteria system for the evaluation of Google QA quality by coding and analyzing search results of questions from a representative question set. The study then evaluated Google’s overall QA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…It was found that Google provided significantly higher-quality answers to person-related questions than to thing-related, event-related, and organization-related questions. Google also provided significantly higher-quality answers to wherequestions than to who-, what-and how-questions [27]. Snippets are also influencing partisanship.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that Google provided significantly higher-quality answers to person-related questions than to thing-related, event-related, and organization-related questions. Google also provided significantly higher-quality answers to wherequestions than to who-, what-and how-questions [27]. Snippets are also influencing partisanship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Featured snippets are displayed in three different forms, i.e. paragraphs [27], tables [23], or lists, either ordered or unordered [46]. In the beginning of featured snippets' introduction into SERPs, Miklosik et al [46] examined the different possible factors for presenting a piece of information from a particular webpage in featured snippets.…”
Section: E Featured Snippetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct answer supposed to deliver answers for keywords, without need to visit the result presented in search engine [17]. This snippet is displayed in four different forms like paragraph [18], table [19] and ordered or unordered list [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Direct answer supposed to deliver answers for queries, without need to visit the result presented in search engine [13]. This snippet can be presented in several different forms like paragraph [14], table [15] and ordered or unordered list.…”
Section: Literature Reviewmentioning
confidence: 99%